Problems Experienced by Undergraduate Students in Conducting Research in Online Distance Learning - Bushra Haleem; Sumbal Asghar (PJDOL, 2023)
This study's aim was to examine the difficulties that undergraduate students had while doing their research in online distance learning environment. This study used a descriptive research design and was quantitative in nature. By using census all 247 students enrolled in different undergraduate degree programs in department of education were selected who have completed research projects as a part of their degree program at Virtual University of Pakistan. In the questionnaire, students were asked about problems faced by them in three domains i.e. student-related, supervisor-related and institution-related. The quantitative data were analyzed using descriptive statistics. The findings of the study revealed that during research conduction the problems faced by students are; lack of discussion with supervisor, lack of time for research, lack of digital library resources, insufficient content and lack of direction, tool/questionnaire selection, accessing resources, unwillingness of participants and problems in writing and reporting the results. Thefindings highlighted the problems of resources that hindered students’ smooth learning progress at VU. It is recommended that institute may provide digital library resources and also upload the theses on its website so students can get help from differentsources during research conduction.